IMPLEMENTATION OF COMMUNICATION MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION AT PAKU STATE VOCATIONAL SECONDARY SCHOOLS, POLEWALI MANDAR DISTRICT (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to: 1) find out how planning in improving the quality of education at SMKN Paku, 2) find out how implementation in improving the quality of education at SMKN Paku. This research took place for 15 days starting from January 2 to January 15, 2023. Located at SMKN Paku, Jln. Poros Pinrang km 15, Silopo, Binuang District, Polewali Mandar, West Sulawesi with 5 (Five) informants. The research method used is descriptive analysis qualitative method, with data collection techniques by conducting observations, interviews and documentation. The results of this study are to form a school development committee and create a work program listed in the scope of improvement and development of SMKN Paku. This work program boils down to increasing links and matches with IDUKA / industry and the relevant world of work, programs that cover aspects.